Usability evaluation of multimodal interactive virtual environments for learners who are blind: An empirical investigation. Issue 158 (February 2022) - Darin, Ticianne; Andrade, Rossana; Sánchez, Jaime
Highlights: Effectiveness of Usability Evaluation Methods differ significantly from each other in Multimodal Interactive Virtual Environments for blind learners Problems disclosed by each Usability Evaluation Methods are associated with specific interaction modalities Video analysis of think-aloud was more effective to assess usability in Multimodal Interactive Virtual Environments for blind learners Interview stood out in assessing satisfaction and learnability in Multimodal Interactive Virtual Environments for blind learners A specialized checklist stood out in assessing graphic and acoustic feedback, and device interaction in Multimodal Interactive Virtual Environments for blind learners Abstract: Multimodal Interactive Virtual Environments (MIVE) have been used to help developing new skills and to stimulate cognitive improvement for learners who are blind. In this scenario, the presence of usability issues in the interaction can jeopardize the development and enhancement of the target cognitive skills. In this paper, we investigate how to evaluate MIVE for education and training of learners who are blind, employing Usability Evaluation Methods (UEM) adequate to the users' individualities and to the evaluation goals. A comparative single-factor within-subject experiment design was used to assess the significance of UEMs effectiveness at three treatments. Interaction data was collected from twenty independent onsite user evaluations, using observation together with a think-aloud protocol, field notes, semi-structured interview and a specialized checklist. As a result, building on previous research, we systematize the main findings and provide a "tool for thought", directions for reasoning about how to use and combine UEMs in usability evaluation in this field, given the context, the target users characteristics and the MIVE features under evaluation.